Hektor na Islandii. Historia Trojańska w źródłach staroislandzkich czyli o tym, jak Snorri Sturluson włączył Skandynawów do antycznego dziedzictwa - Słupecki, Leszek (Studia Europaea Gnesnensia, 2012)
The paper acquaints Polish readers with how Snorri Sturluson used the Trojan myth in his Edda; developing his version of it in the Prologue and using it as a frame story of Gylfaginning. The paper shows the medieval reception of the Trojan myth (Dictys, Dares), the background of Trojan myth inIceland (Trojumanna saga, Bretta sogur), and medieval strategies of using theTroymyth to demonstrate ancient origins of own nations, which, in emulation of the Romans was done by the Franks and the Britons. Snorri employs this myth for the sake of Scandinavians, developing euhemeristic story about the Æsir showing them as clever people fromTroy. To him it was rather a tool to underline the ancient descent of Scandinavian elites, a trick giving him the reason to write a long text about Old Norse paganism in Christian setting. For the author of the paper Snorri is undoubtedly the author of the Prologue. Some Frankish influence is suspected to be among the sources for his tale ofTroy.